Musculoskeletal Disorders and Associated Factors among Vehicle Repair Workers in Hawassa City, Southern Ethiopia - Tamene, Aiggan (J Environ Public Health, 2020)
BACKGROUND: Vehicle repair work is one of the highest risk professions for work-related musculoskeletal disorders. Globally, only a few published studies have examined the prevalence and determinants of work-related musculoskeletal disorders among vehicle repair workers. Related studies in Ethiopia are even fewer. This study aimed to determine the prevalence of self-reported work-related musculoskeletal disorders and associated factors among vehicle repair workers in Hawassa city, South Ethiopia, 2019. METHODS: An institution-based cross-sectional study was conducted among 344 vehicle repair workers in the Hawassa city. The Nordic Musculoskeletal Questionnaire-Extended (NMQ-E) was used to assess work-related musculoskeletal disorders on nine body regions. Descriptive statistics and multivariable analyses were used to characterize the data and identify factors associated with work-related musculoskeletal disorders. RESULT: The twelve-month prevalence of work-related musculoskeletal disorders among this working group was 47.7% with 95% CI (42.7–53.2). Jobs continuously requiring repetitive motions (AOR: 4.29, 95% CI (1.78–10.2)), not having professional training (AOR: 2.04, 95% CI (1.09–3.81)), force exertion when using tools (AOR: 2.40, 95% CI (1.24–4.62)), job stress (AOR:4.54, 95% CI (2.44–8.46)), and regularly lifting, pushing, and pulling loads greater than 20 kg (AOR:4.85, 95% CI (2.65–8.87)) were identified as associated factors. CONCLUSION: This study showed a 47.7% prevalence of work-related musculoskeletal disorders. Force exertion, repetitive tasks, manual handling of heavy loads, stress, and lack of training were the identified factors. Ergonomic awareness among workers should be increased through training. In addition, owners should investigate methods to reduce or eliminate risk factors leading to musculoskeletal disorders found among these workers. Automation of high-risk tasks should also be investigated.